Thermo-mechanical analysis of the Andean lithosphere over the Chilean-Pampean flat-slab region - Sanchez, Marcos Ariel (2017)
Flat subduction segments are generally related to cold lithospheric zones, which suggest low Heat flow values and therefore a deeper Curie isotherm. In this study we perform a geophysical analysis by using high - resolution magnetic data, obtaining shallower Curie point depths through the Chilean-Pampean flat-slab zone. Then using temperatures from borehole data and Curie Point Depths, we performed a Heat Flow map which indicates the existence of mean to high thermal anomalies across the Chilean - Pampean flat-slab. These results were contrasted with Elastic Thickness map (Te) obtained from the Eigen-6C4 gravity model. Low Te values acquired indicate zones with weak mechanical behavior in correspondence to thermal anomalous zones. This spatial correlation suggests that the local high thermal anomalies are conditioning the mechanical behavior of the lithosphere in the study area and the locations of geothermal sources. Overall, our results indicate that the thermal structure of the flat-slab segment is more heterogeneous than previously thought. This has implications for evolution, maturity and fluid circulation in foreland basins of the Main and Frontal cordilleras and the Precordillera thrust belts. Finally, further studies will allow improving our database as well as extending our understanding of the thermal structure of the Chilean-Pampean flat-slab.